Beyond Exoticism: Western Music and the World. Taylor, Timothy D. 2007. Durham: Duke University Press. xv, 304 pp., 16 illustrations, notes, bibliography, index. - Watkins, Lee (International Library of African Music, 2007)
pages: 122-127
Keywords: African Music